A Study On Emotional Intelligence Of Employees Of Milk Marketing Federation At Kalady. - et. al., Ms. Suma Menon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Emotional Intelligence (EI) is important for professional and personal achievement. It may be the most essential attribute of all, but it is rather abstract, making it impossible to deal with and difficult to demonstrate. Equivalent represents a person's capacity to detect and react to feelings appropriately. This level of emotional vulnerability and compassion is important for high levels of cooperation and efficiency. All accomplished leaders and top performers share a range of highly established comparable skills. Their glorious counterpart is essential for working successfully with a diverse group of people. It is also important for preserving equilibrium and responsiveness in today's corporate world, which is marked by strict competitive situations. As a result, employees' emotional maturity is critical to a company's success. The emotional intelligence of staff at the Milk Marketing Federation project in Kalady is the problem area of this study. The research was completed in order to determine the emotional maturity of organizational employees, as well as to examine the relationship between perception and self-regulation, self-motivation and self-regulation, and compassion and relationship management.